Academic Information Systems Management at IAIN Curup - Permanasari, Revi; Warsah, Idi; Warlizasus, Jumira (Journal of English Language and Education, 2025)
Academic Information System (AIS) is an important element in supporting efficient, structured, and transparent academic data management in higher education institutions, including Islamic Religious Colleges (PTKI). This study aims to analyze the AIS management strategy at the State Islamic Institute (IAIN) Curup in four main dimensions, namely planning, implementation, evaluation, and follow-up. The research method used is qualitative with a case study approach. Data were obtained through in-depth interviews, direct observation, and documentation of 50 informants consisting of heads of study programs and administrative staff from various faculties. The results of the study indicate that there are still weaknesses in strategic planning, uneven implementation in terms of infrastructure and human resource competencies, and an evaluation process that is not yet based on standardized performance indicators. On the other hand, the follow-up to the evaluation is still partial and less systematic. These findings emphasize the need to optimize the AIS management system through a data-based approach and integration between human, technology, and process components. This study provides a strategic contribution to the development of a more responsive and adaptive AIS in the PTKI environment.